Influence of sowing date on seed yield and quality in onion (Allium cepa L.) by production "seed to seed" method - Ilić Zoran; Šunić Ljubomir; Milenković Lidija; Gvozdanović-Varga Jelica (Selekcija i Semenarstvo, 2006)
The experiments took into account four cultivars origin from different agroclimacteric regions, usually grown in our country (Prizrenski pogačar, Kupusinski jabučar, Trebinjska kapula and Holandski žuti), are The sowings were realized on 15 July (first term), 5 August (second) and 25th August (third). Sowings were carried out in rows 45cm apart and 5cm apart along the row (number of plants 44,8/m2). Experimen was split-plot designed with three replicaties. Gibberellic acid-GA3 sprays were applied with concentration at 50ppm on plants at the 6-7 leaves stage. Yield and its principal components were analyzed (percentage of flowering, capsules/umbel, seed/capsule, 1000 seed weight, germination energy, germination). Flowering percentage in the two years was affected by sowing date. Sowing postponement from July to August caused a reduction in the flowered plant from 90% to 40%, which produced only one umbel per plant. Sowing-flowering-seed ripening was reached almost simultaneously after 405-370 days. Seed production was highest in the first term sowing from 15 July for all cultivars. The cultivars showed differences in both years. Cultivar Kupusinski jabučar obtained the highest yield in the first term sowing - 440,4 kg/ha (in first year), while Holandski žuti obtained significantly lower in the third term from 25 August with only 140,6kg/ha (in first year).